2004
DOI: 10.1128/jvi.78.18.9763-9772.2004
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 gp120 Induces Abnormal Maturation and Functional Alterations of Dendritic Cells: a Novel Mechanism for AIDS Pathogenesis

Abstract: Dendritic cells (DCs) play a crucial role in bridging innate and acquired immune responses to pathogens. In human immunodeficiency virus type 1 (HIV-1) infection, immature DCs (iDCs) are also main targets for HIV-1 at the mucosal level. In this study, we evaluated the effects of HIV-1-DC interactions on the maturation and functional activity of these cells. Exposure of human monocyte-derived iDCs to either aldrithiol-2-inactivated HIV-1 or gp120 led to an upmodulation of activation markers indicative of functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
95
3
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 44 publications
11
95
3
2
Order By: Relevance
“…Granelli-Piperno et al have recently found similar results with infectious HIV-1 BaL particles, 16 whereas others have observed an augmentation of CD83 expression in the presence of high concentrations of recombinant gp-120 or inactivated HIV particles. 5,17 In the presence of concentrations of IgG that result in a 90% reduction of HIV-1 infection, no maturation of MDDCs was detected 24 or 64 hours after infection, indicating that the inhibition of HIV replication by these IgGs was not due to MDDC maturation. Nevertheless, at high concentrations of mAb 2F5 (100 g/mL) or polyclonal IgG (650 g/mL), an increased percentage of CD83 ϩ and DC-LAMPpositive MDDCs was measured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Granelli-Piperno et al have recently found similar results with infectious HIV-1 BaL particles, 16 whereas others have observed an augmentation of CD83 expression in the presence of high concentrations of recombinant gp-120 or inactivated HIV particles. 5,17 In the presence of concentrations of IgG that result in a 90% reduction of HIV-1 infection, no maturation of MDDCs was detected 24 or 64 hours after infection, indicating that the inhibition of HIV replication by these IgGs was not due to MDDC maturation. Nevertheless, at high concentrations of mAb 2F5 (100 g/mL) or polyclonal IgG (650 g/mL), an increased percentage of CD83 ϩ and DC-LAMPpositive MDDCs was measured.…”
Section: Discussionmentioning
confidence: 99%
“…13,16 Moreover, abnormal maturation induced by LPS has been measured after exposure of iMDDCs to HIV-1 gp-120. 17,18 Recently, it has been shown that LPSinduced maturation could be prevented by addition of recombinant Vpr. 19 Thus, new evidence has shown that HIV-1 could interfere with DC immune responses by impairing their maturation process, their cytokine production, and their allogenic T-cell stimulatory function; this could contribute to immune dysfunction in AIDS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some human immunodeficiency virus type 1 proteins influence specific functions of DCs. Vpr prevents expression of the costimulatory molecules CD80, CD83, and CD86 at the transcriptional level without altering normal cellular transcription (40); glycoprotein gp120 induces an impaired ability to secrete cytokines or chemokines, and as a consequence, T-cell stimulation is reduced (24).…”
Section: Discussionmentioning
confidence: 99%
“…Both cytokines were kindly provided by Schering-Plough (Dardilly, France). On day 6, MDDCs were stimulated with lipopolysaccharide (LPS; 10 ng/ml), gp120 (5 g/ml, unless otherwise indicated), AT-2-inactivated HIV-1 BaL (46.783 ng/ml p24) (22), or CCL4 (100 nM). Monocyte-derived macrophages (MDMs) were obtained after 6 days of in vitro culture in endotoxin-free Iscove's medium containing 10% FBS as previously described (23).…”
Section: Methodsmentioning
confidence: 99%
“…The HIV-1 BaL virus preparation were purchased from ABI (Columbia, MD) and inactivated as previously described (22).…”
Section: Methodsmentioning
confidence: 99%